Solid state synthesis of 50Ti-50Zr binary alloy by mechanical alloying in inert atmosphere - Wibowo, Anton. (2009)
Earlier studies have reported metastable hexagonal close packed (HCP) to face centered cubic (FCC) polymorphic transformation in elemental Ti and Zr as they are mechanically alloyed. This project was done to investigate the transformation in 50Ti-50Zr powder mixture and 50Ti-50Zr alloy was produced by solid state synthesis via mechanical alloying from elemental Ti and Zr powders. Using a combination of X-ray diffraction analysis, secondary electron microscopy techniques and differential thermal analysis, the mechanically induced solid-state reaction was studied. Results showed that FCC 50Ti-50Zr was obtained after being mechanically alloyed for 120 hours. The polymorphic transformation was similar to the elemental Ti and Zr. The average particle size generally decreased with increasing milling time, with an anomaly point at milling time = 20 hours. The crystalline size of 50Ti-50Zr decreased and lattice strain increased with increasing milling time. It was suggested that the transformation of 50Ti-50Zr is similar with the elemental Ti and Zr because of the complete solid solution formed when Ti and Zr form an alloy. The DTA for powder mixture before milling and after milling for 120 hours showed a shift in the exothermic transition peaks.